Differential contributions of the two hemispheres in intra-modal proprioceptive sensory matching in 7–10-year-old boys - Waal, A; Sigmundsson, H; Whiting, H.T.A (Behavioural brain research, 2000)
This study explores putative differential contributions of the two hemispheres when 7–10-year-old right-hand and left-hand preferent boys are required to carry out a ‘foot-hand’ target location and matching task. The task required subjects to locate a target pin with the big-toe (felt target), and match the located target position with the hand, without vision. Right-handed ( n=25) and left-handed ( n=22) boys were tested in a four-condition design. Two intra-hemispheric conditions (right foot locating–right hand matching, left foot locating–left hand matching), and two inter-hemispheric conditions (right foot locating–left hand matching, left foot locating–right hand matching) were used. When the criterion for handedness was writing hand only the results were found to be confounded by the large number of subjects with indeterminate handedness (isolated by use of the Edinburgh Handedness Inventory) originally assigned to the left-handed group. Reclassification of the handedness groups, on the basis of this inventory, showed the pure-left handers to be as good on those conditions mediated by the right hemisphere as pure right handers were with those conditions mediated by the left. These findings are discussed with respect to the contention that left handers are not just ‘reversed’ right handers.